IMPLEMENTASI ISAK 35 PADA YAYASAN IKATAN PERSAUDARAAN HAJI INDONESIA MADIUN - Nurharibnu Wibisono; Hidayatul Alveniawati; Arini Wildaniyati (JURNAL EKOMAKS Jurnal Ilmu Ekonomi Manajemen dan Akuntansi, 2022)
The goal of this study is firts, to know the management of financial of the Madiun Indonesian Hajj Brotherhood Foundation (IPHI). Second, To obstain the processing of financial statement at the Indonesian Hajj Brotherhood Foundation in Madiun with financial statements according to ISAK 35. This study is a qualitative analysis that purposes to answer questions regarding financial management at the foundation and the suitability of its financial management based ISAK 35. Collecting data through observation, interviews also with documentation. The data is processed by means of descriptive analysis. The output of research show that the Financial Statements based on ISAK 35 consist of various inform including balance sheet, report of comprehensive income, statement of changes in net assets, report of cash flows also notes to financial reports. However, the IPHI Madiun Foundation has not made the 5 (five) financial reports based on applicable standards. IPHI Madiun Foundation only makes cash in and cash out finacial reports. Accountability within the IPHI Madiun Foundation has not been carried out optimally, as evidenced by the absence of disclosure of financial conditions to the public or to donors. Recommendation that can be given are in terms of preparing financial report in conformability with ISAK 35, it can be done by participating in training which is hope to improve knowledge in the field of accounting. With ISAK 35 the IPHI Madiun Foundation may be give directives to the presentation of financial statements, and the IPHI Madiun Foundation will be more obedient to the regulations so that accountability can be obtained.